2019
DOI: 10.1016/j.jid.2019.03.1159
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingosine-1-Phosphate Receptor Modulator Fingolimod Aggravates Murine Epidermolysis Bullosa Acquisita

Abstract: clear DEAF-1-related (NUDR) protein contains a novel DNA binding domain and represses transcription of the heterogeneous nuclear ribonucleoprotein A2/B1 promoter. J Biol Chem 1999;274:30510e9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…One possibility to observe potential exchanges of Tfh cells between lymph nodes would be treatment with the T cell trafficking blocker FTY720. However, previous studies revealed no effect in this autoimmune mouse model ( Niebuhr et al, 2017 ; Thieme et al, 2019 ). The second major finding of our study is that the PBS group, which received only adjuvant, develops GCs to a similar extent as the Ag group.…”
Section: Discussioncontrasting
confidence: 61%
“…One possibility to observe potential exchanges of Tfh cells between lymph nodes would be treatment with the T cell trafficking blocker FTY720. However, previous studies revealed no effect in this autoimmune mouse model ( Niebuhr et al, 2017 ; Thieme et al, 2019 ). The second major finding of our study is that the PBS group, which received only adjuvant, develops GCs to a similar extent as the Ag group.…”
Section: Discussioncontrasting
confidence: 61%
“…Recent studies in mouse models of pemphigoid diseases, have highlighted the anaphylatoxin C5a and the eicosanoid leukotriene B 4 as central choreographers of this process on the molecular level (9,11,12). On the cellular level, γδ T cells and T regs have been demonstrated to interact with granulocytes to promote and suppress skin inflammation, respectively, by modulating neutrophil activity in the dermis (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, S1P receptors have been studied in relation to pathological mechanisms in various tissues and diseases. In the field of dermatology, S1P receptors have been reported to affect various skin diseases, including wound [27], scleroderma [28], epidermolysis bullosa [29], infection [30,31], and inflammatory skin diseases such as atopic dermatitis [32][33][34][35][36] and psoriasis [37][38][39][40]. Recently, Reines et al reported that the topical application of S1P and S1P modulator, FTY720, which binds to S1PR1 and has mixed agonist-antagonist effects on S1PR1 [41], but also binds to S1PR3-5 as well, attenuated ACD reaction via inhibiting dendritic cell migration [42].…”
Section: Discussionmentioning
confidence: 99%